Chronic fine particulate matter exposure, habitual exercise, and dyslipidemia: A longitudinal cohort study. Issue 1 (5th February 2022) - Zeng, Yi Qian; Chang, Ly-yun; Guo, Cui; Lin, Changqing; Bo, Yacong; Wong, Martin C. S.; Tam, Tony; Lau, Alexis K. H.; Lao, Xiang Qian
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Physical activity may increase the intake of air pollutants due to a higher ventilation rate, which may exacerbate the adverse health effects. This study investigated the combined effects of habitual exercise and long-term exposure to fine particulate matter (PM2.5 ) on the incidence of dyslipidemia in a large longitudinal cohort in Taiwan. Methods: A total of 121, 948 adults (≥18 years) who received at least two medical examinations from 2001 to 2016 were recruited, yielding 407, 821 medical examination records. A satellite-based spatiotemporal model was used to estimate the 2-year average PM2.5 concentration (i.e., the year of and the year before the medical examination) at each participant's address. Information on habitual exercise within 1 month before the medical examination was collected using a standard self-administered questionnaire. A Cox regression model with time-dependent covariates was used to investigate the combined effects. Results: Compared with inactivity, moderate and high levels of exercise were associated with a lower incidence of dyslipidemia, with hazard ratios (HRs) (95% confidence intervals [CIs]) of 0.91 (0.88, 0.94) and 0.73 (0.71, 0.75), respectively. Participants with a moderate (22.37–25.96 μg/m 3 ) or high (>25.96 μg/m 3 ) level of PM2.5 exposure had a higher incidence of dyslipidemia than those with a low level of PM2.5 exposure (≤22.37 μg/m 3 ), with HRs (95% CIs) of 1.36 (1.32, 1.40), and 1.90 (1.81, 1.99), respectively. We observed a statistically significant, but minor, interaction effect of PM2.5 exposure and exercise on the development of dyslipidemia, with an overall hazard ratios (95% CI) of 1.08 (1.05, 1.10), indicating that an incremental increase in the level of exercise was associated with an 8% increase in the risk of dyslipidemia associated with every 10 μg/m 3 increase in PM2.5 exposure. However, the negative association between habitual exercise and dyslipidemia remained, regardless of the level of PM2.5 exposure, suggesting that the benefits of increased habitual exercise outweighed the adverse effects of the increase in PM2.5 intake during exercise. Conclusions: Increased levels of exercise and reduced levels of PM2.5 exposures were associated with a lower incidence of dyslipidemia. Although an increase in habitual exercise slightly increased the risk of dyslipidemia associated with PM2.5 exposure, the benefits of the increased habitual exercise outweighed the risks. Our findings suggest that habitual exercise is an effective approach for dyslipidemia prevention, even for people residing in relatively polluted areas.